2009
DOI: 10.1177/0022034508331011
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Dental Caries Progression in Primary Teeth

Abstract: The current evidence on the role of the social, behavioral, and community determinants of dental caries is based on cross-sectional analyses. The available evidence has not been based on analysis of multiple determinants within the same population. This longitudinal study addresses both of these limitations. The study included data from 788 dyads of children and their caregivers (77% follow-up), who were examined in 2002–03 and 2004–05. The families were assessed by calibrated dentists for severity of caries a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
102
3
12

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(124 citation statements)
references
References 22 publications
7
102
3
12
Order By: Relevance
“…In the present study, the presence of cavitated carious lesions at baseline was also significant for the increased An early childhood caries study rate of progression of caries lesions at two-year follow-up compared to children with initial lesions at baseline. Similar results were found in several studies, which also showed that the presence of caries lesions at baseline increased the caries increment after the follow-up period (1,(5)(6)(7)(8)11,24).…”
Section: An Early Childhood Caries Studysupporting
confidence: 89%
See 3 more Smart Citations
“…In the present study, the presence of cavitated carious lesions at baseline was also significant for the increased An early childhood caries study rate of progression of caries lesions at two-year follow-up compared to children with initial lesions at baseline. Similar results were found in several studies, which also showed that the presence of caries lesions at baseline increased the caries increment after the follow-up period (1,(5)(6)(7)(8)11,24).…”
Section: An Early Childhood Caries Studysupporting
confidence: 89%
“…Thus, evaluating the oral health of preschool children is important because the experience of caries in primary teeth has been considered the strongest predictor of caries in permanent teeth and this was confirmed by several longitudinal studies conducted in different countries (1,(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Seven cohort studies in eleven publications were identified that presented evidence on the relationship between sugars-containing beverage consumption and the incidence of dental caries in deciduous dentition in children, all of which adjusted their results for tooth brushing (Grytten et al, 1988;Grindefjord et al, 1995;Grindefjord et al, 1996;Tada et al, 1999;Levy et al, 2003;Mariri et al, 2003;Sakuma et al, 2007;Ismail et al, 2008;Warren et al, 2008;Lim et al, 2008;Ismail et al, 2009). Three cohorts were reported in more than one publication: (Grindefjord et al, 1995;Grindefjord et al, 1996) reported on one cohort; Lim et al, 2008;Ismail et al, 2009) reported on one cohort; and (Mariri et al, 2003;Levy et al, 2003) reported on one cohort. The data on measures of dietary exposure, caries incidence/prevalence and risk assessment methods were insufficiently comparable to enable a meta-analysis to be performed.…”
Section: Sugars-sweetened Beverages and Bmimentioning
confidence: 99%